Banyumas Regency Tourism Potential - Khosy Zufar Annaafi (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
In line with the government's program to develop creative industries in Indonesia until 2025. The tourism industry is expected to be one of the triggering industries for creative economic growth. This journal aims to provide an overview of the tourism industry and economic activities related to this industry in the Banyumas Regency. The data used in the form of hotel occupancy data, length of stay of tourists, and number of tourists taken from the Banyumas Regency BPS. The data is used to find out how big the impact of tourism is on the community. Banyumas Regency's tourism industry still relies on natural tourism. Some of the attractions that are in need of attention of local governments because of conditions that are not maintained, thus reducing the interest of visitors. Various tourism potentials are still being developed such as a culture that blends from Javanese culture and Sundanese culture and also a combination of natural tourism and cultural tourism can develop